Charting freedom: inequality beliefs, preferences for redistribution, and distributive social policy in contemporary South Africa - Roberts, Benjamin J (Rhodes University, Faculty of Humanities, Institute of Social and Economic Research, 2019)
While the transition to democracy in South Africa extended civil and political rights and freedoms to all South Africans, there has been disagreement over the preferred nature and scope of social rights within post-apartheid society, reflecting debates over the trajectory of economic policy. Appreciable developmental gains have been made by the state over the last quarter-century, yet the challenges of poverty, unemployment and inequality persist, coupled with mounting popular discontent with the pace of transformation and political accountability. This has led to fundamental questions about social justice, restitution, and the kind of society we wish to promote. Appeals for a more inclusive, transformative social policy have also emerged, arguing that a wider vision of society is required involving multiple government responsibilities and informed by an ethic of equality and social solidarity. Against this background, in this thesis I study the views of the South African public towards economic inequality, general preferences for government-led redistribution, as well as support for social policies intended to promote racial and economic transformation. The research has been guided by several overarching questions: To what extent do South Africans share common general beliefs about material inequality? Does the public exhibit a preference for government redistribution in principle? And how unified or polarised are South Africans in their support for specific redress policies in the country? Responding to these questions has been achieved by drawing on unique, nationally representative data from the South African Social Attitudes Survey (SASAS), which has enabled me to chart social attitudes over a period of almost fifteen years between late 2003 and early 2017. Use has also been made of social citizenship as a guiding conceptual framework to understanding social policy predispositions and analysing attitudinal change. The results demonstrate that the public is united in its awareness of and deep concern about economic inequality. Since the early 2000s, a significant majority has consistently expressed the view that the income gap in the country is too large, articulated a strong preference for a more equitable social structure, and acknowledged the class and social tensions that economic inequality has produced. There is also a preference for a narrowing of earnings disparities, a more generous minimum wage, and regulatory limits on executive pay. While this suggests a desire for fair and legitimate remuneration, the analysis also reveals that South Africans are willing to tolerate fairly high levels of inequality. Nonetheless, these beliefs are generally interpreted as a desire for a more equitable and fair society. This preference for change is reflected in a fairly strong belief that government should assume responsibility for reducing material disparities. One's social position, mobility history, awareness of inequality, political leaning and racial attitudes all have a bearing on how weak and strong this predisposition is, but the normative demand for political redistribution remains fairly widely shared irrespective of these individual traits. Greater polarisation is however evident with respect to redistributive social policy, especially measures designed to overcome historical racial injustice (affirmative action, sports quotas, and land reform). These intergroup differences converge considerably when referring to class-based policy measures. One surprising finding is the evidence that South Africa's youngest generation, the so-called 'Born Frees', tend to adopt a similar predisposition to redress policy as older generations, thus confounding expectations of a post-apartheid value change. I conclude by arguing that there seems to be a firmer basis for a social compact about preferences for interventions designed to produce a more just society than is typically assumed. Intractably high levels of economic inequality during the country's first quarter-century of democracy is resulting in a growing recognition of the need for a stronger policy emphasis on economic inequality in South Africa over coming decades if the vision enshrined in the Freedom Charter and the Constitution is to be realised. South Africans may not be able to fully agree about the specific elements that constitute a socially just response to economic inequality. Yet, the common identification of and concern with redressable injustice, coupled with a broad-based commitment to government redistribution and classbased social policies, could serve as a foundation on which to rekindle the solidaristic spirit of 1994 and forge progress towards a more equitable society.
Keywords: South Africa -- Economic conditions; South Africa -- Economic policy; South Africa -- Social policy; Democracy -- Economic conditions -- South Africa; Race discrimination -- South Africa; Poverty -- South Africa; Equality -- South Africa